Immunostimulatory CpG oligodeoxynucleotides enhance the induction of bovine CD4+ cytotoxic T-lymphocyte responses against the polymorphic immunodominant molecule of the protozoan parasite Theileria parva - Graham, S.P.; Saya, R.; Awino, Elias; Ngugi, D.; Nyanjui, J.K.; Hecker, R.; Taracha, E.L.N.; Nene, Vishvanath M. (Elsevier, 2007)
Enhancement of the induction of cytotoxic T-cell responses by immunostimulatory CpG oligodeoxynucleotides has been described in humans and mouse models. The present study attempted to address whether CpG has a similar effect in cattle. Immunisation of cattle with a recombinant form of the polymorphic immunodominant molecule from Theileria parva emulsified with immunostimulatory CpG oligodeoxynucleotides in adjuvant had no effect on the induction of antibody responses including the isotype profile, but significantly enhanced the induction of cytolytic responses that were mediated by CD4+CD3+ T cells utilizing the perforin-granzyme pathway.